2014
DOI: 10.1017/s0308210512000285
|View full text |Cite
|
Sign up to set email alerts
|

A note on the Abresch—Langer conjecture

Abstract: A saddle-point property of the self-similar solutions in the curve shortening flow was conjectured by Abresch and Langer and confirmed by Au. An improvement on Au's solution is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…We finally mention that, after Abresch and Langer's celebrated study [1], the behavior of multiply winding rotationally symmetric curves is investigated by several authors for the curve shortening flow [3,20,24,25,44,45] and other second order geometric flows [13,[46][47][48]; in particular, a kind of stability result for multiply covered circles is obtained by Wang [45], in the same spirit of our result. We remark that all these studies focus on locally convex curves, thus using the property of second order.…”
Section: Curve Diffusion Flowsupporting
confidence: 71%
“…We finally mention that, after Abresch and Langer's celebrated study [1], the behavior of multiply winding rotationally symmetric curves is investigated by several authors for the curve shortening flow [3,20,24,25,44,45] and other second order geometric flows [13,[46][47][48]; in particular, a kind of stability result for multiply covered circles is obtained by Wang [45], in the same spirit of our result. We remark that all these studies focus on locally convex curves, thus using the property of second order.…”
Section: Curve Diffusion Flowsupporting
confidence: 71%
“…We finally mention that, after Abresch and Langer's celebrated study [1], the behavior of multiply winding rotationally symmetric curves is investigated by several authors for the curve shortening flow [25,24,3,44,45,20] and other second order geometric flows [47,48,13,46]; in particular, a kind of stability result for multiply covered circles is obtained by Wang [45], in the same spirit of our result. We remark that all these studies focus on locally convex curves, thus using the property of second order.…”
Section: Introductionsupporting
confidence: 72%
“…Recently, the asymptotic stability of multi-circles has been proved by Wang [13]. And the saddle point property of Abresch-Langer curves (first conjectured by Abresch-Langer [11]) has been confirmed by Au [14] and improved by Chou-Wang [15]. We must also notice that in 1987, Epstein and Gage [16] showed that a highly symmetric, locally convex curve must evolve into a round point.…”
mentioning
confidence: 93%
“…An example is the pentagram. In fact, the works of [13][14][15] and of Epstein-Gage [16] supply a picture for what type of curves can evolve into round points.…”
mentioning
confidence: 99%